Assessing the effect of high school quality factors in selecting a high school - Melitina Tecoalu (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of education quality, price, promotion strategy, quality of human resources, and physical facilities mediated by reputation on students' decision to select a high school. The research technique used to obtain data from 170 prospective students is purposive sampling, a non-probability method. The results showed that the education quality, promotion strategies, and physical facilities mediated by reputation positively affect students' decisions, as opposed to the price and quality of human resources. The originality value of this research is to choose high school mediation by reputation. In conclusion, the limitations of this research were clarified by adding a process variable which is very important in services marketing, due to its ability to handle consumers in marketing activities and in making final decisions.